STUDENTS` SELF-CREATED YOUTUBE VIDEOS: A 21st CENTURY SPEAKING ASSESSMENT - Rajulain, Muhammad (Diksi, 2020)
(Title: Students` Self-Created Youtube Videos: A 21st Century Speaking Assessment). The Regulation of the Minister for Education and Culture Affair number 69 2013, which regulates the Basic Framework and Curriculum Structure of High School/ Islamic High School, has regulated English subjects meeting which is now trimmed to 2 hours meeting in a week which was 4 hours meetings prior to the implementation of this regulation. The teachers, therefore, are expected to adapt to this new regulation in improving their students` speaking skill. Information and Technology rapid advancement has allowed the teachers to apply it in teaching and learning process. This paper is therefore aimed at describing the employment of Information and Technology (YouTube) in assessing students` speaking skill.Keywords: speaking skill, youtube, assessment